The chemical constituents and the cytotoxicity, antioxidant and antibacterial activities of the essential oil of Graptophyllum pictum (L.) Griff - Jiangseubchatveera,N. (Har Krishan Bhalla and Sons, 2015)
© 2015, © 2015 Har Krishan Bhalla & Sons. The essential oil from the leaves of Graptophyllum pictum (L.) Griff. was isolated by hydrodistillation and its chemical constituents were investigated by a combination of gas chromatographic (GC-FID) and gas chromatography-mass spectrometric (GC-MS) analysis. Fourteen compounds, comprising 95.0 % of the gas chromatographical oil, were identified. The major constituents were phytol (75.7 %), n-nonacosane (6.5 %) and hexahydrofarnesyl acetone (2.6 %). The oil showed significant cytotoxicity against KB (epidermoid carcinoma of oral cavity), NCI-H187 (small cell lung carcinoma) and Vero cell lines with IC50 values of 27.04, 25.27 and 26.52 µg/mL, respectively. The antioxidant activity of the oil was determined using the ABTS radical cation scavenging assay. The oil had less antioxidant activity than the controls, trolox and ascorbic acid. In a disc diffusion assay the oil exhibited antibacterial activity against S. aureus and E. coli with MIC values of 11.75 and 35.25 µg/disc, respectively.